Implementasi Smart and Green University pada Universitas Sultan Ageng Tirtayasa Banten - Yanuwardhana, Sahala Mimbar; Waseh, Hasuri (Epistemik Press, 2024)
The aim of this research is to understand how the Smart & Green University concept is implemented in the Sindangsari Campus Area of ​​Sultan Ageng Tirtayasa University. This research focuses on the implementation of the green campus program, which is part of Untirta's vision and mission, namely realizing Untirta as a Healthy, Integrated, Smart and Green University (HITS Green) that is Superior, Characteristic and Globally Competitive by 2035. The theory that became the foundation is the theory of policy implementation by Merilee S. Grindle. The method used is descriptive qualitative with data collection techniques through observation, interviews and literature study. The research results show that the implementation of the green campus program is still not optimal. Oversight efforts lack clarity regarding who is responsible. UPT Smart Green and SDGs also failed to carry out effective supervision due to lack of authority. Internalization efforts by UPT Smart Green and SDGs are not effective. Facilities and infrastructure supporting the green campus program throughout the Untirta campus are still inadequate. The budget for this unit is still insufficient. Socialization efforts to increase understanding of the green campus program are still lacking. Lack of preparedness for mediators between leaders and the lowest stakeholders. Several aspects of the 6 green campus criteria need to be improved to achieve the target. Internalization of green campus values ​​among campus residents is still lacking, especially among lecturers and students.